Pengajaran Tentang Hari Penghakiman (Amos 5:18—20) - Gusti Dametriana Sihombing; Erickson Nanda Putra Halawa; Grecetinovitria M. Butar-butar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Judgment is the process of assessing a person's wrongdoing and determining an appropriate punishment, both in worldly and spiritual contexts. In Christianity, the Day of Judgment is when God fully reveals the truth and gives the final verdict on each individual's fate based on their deeds. The Book of Amos, written around the 750s BC by the prophet Amos, warns Israel that the